Digital assemblages, information infrastructures, and mobile knowledge work. (September 2022) - Jarrahi, Mohammad Hossein; Sawyer, Steve; Erickson, Ingrid
We theorize mobile knowledge workers' uses of digital and material resources in support of their working practices. We do so to advance current conceptualizations of both "information infrastructures" and "digital assemblages" as elements of contemporary knowledge work. We focus on mobile knowledge workers as they are (increasingly) self-employed (e.g., as freelancers, entrepreneurs, temporary workers, and contractors), competing for work, and collaborating with others: one likely future of work that we can study empirically. To pursue their work, mobile knowledge workers draw together collections of commodity digital technologies or digital assemblages (e.g., laptops, phones, public WiFi, cloud storage, and apps), relying on a reservoir of knowledge about new and emergent means to navigate this professional terrain. We find that digital assemblages are created and repurposed by workers in their infrastructuring practices and in response to mobility demands and technological environments. In their constitution, they are generative to both collaborative and organizational goals. Building from this, we theorize that digital assemblages, as individuated forms of information infrastructure, sustain stability and internal cohesion even as they allow for openness and generativity.